Morphological Characterization and Socio-Economic Analysis of Horse (Equus caballus) Population from Arsi Highlands, Central Ethiopia: Research article - Bedassa Gudeta, Temesgen; Diriba, Wagari (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2024)
In Ethiopia, horses are among the most significant equines for supporting the livelihood of many smallholder farmers. The study was focused to characterize horse genetic resources of Arsi highlands of Ethiopia based on morphometric traits and analyze their socio-economic importance to enhance horse conservation and breeding objectives. Purposive sampling was used to select the study kebeles from which 270 households and 396 adult horses were selected. The majority (87.7%) of the households in the study area were male headed as the overall average number of horses per individual was (2.20±0.07) and horses are mainly used for riding, cash income and cart pulling. The coat colours varied across the districts where chestnut (43.9%), bay (15.40%), and (14.14%) across the districts. Aggregate means for sex among horses indicated there was no significant difference (p<0.05) in all morphometric traits across the study districts except height at withers exhibited significantly lower for Digaluna Tijo horses. The correlation between morphometric traits was higher in male than female participants. The majority (38.52%) of the horse owners were unable to read and write. The lack of formal education within the horse rearing farmers in the study districts was observed as a reason might have deterred the proper use and conservation of horse genetic resources. The existence of morphometric similarity among horse populations across the study districts could be due to the similarity in the agro-ecology and management practices which further requires characterization at genetic and molecular levels.